Paleoproterozoic post-orogenic magmatism in southern Finland; geochemical, geochronological and Sr-Nd isotopic constraints on origin and magmatic evolution - Oliver Teräs; Kaisa Nikkilä; Perttu Mikkola; Anna Kotilainen; Olav Eklund; O. Tapani Rämö (Bulletin of the Geological Society of Finland)
Fifteen post-orogenic, basic to acidic High-Barium-Strontium (HiBaSr) intrusions of shoshonitic affinity have been recognized in central and southern Finland. Most of the intrusions are found in a 500 km long E–W-trending belt in the Southern Finland Subprovince, with three of them in the Western Finland Subprovince. These rocks have distinctive field, mineralogical, chemical, geochronological and isotopic characteristics compared to the other plutonic rocks in the area. New zircon U-Pb LA-ICP-MS data for two of the intrusions confirm their post-orogenic age: 1805 ± 4 Ma for the Tistronskär biotite-hornblende monzodiorite and 1794 ± 13 Ma for the fluorite-bearing Loukee biotite granite. These rocks plot predominantly in the shoshonitic field and have relatively high K2O (~2.3 wt.%) in the basic varieties, increasing to ~5.0 wt.% in more acidic types. The Tistronskär monzodiorite and Loukee granite show similar geochemistry (high K, Ti, P, Ba, Sr and LREE) to other shoshonitic rocks in southern Finland. These geochemical characteristics, along with an initial 87Sr/86Sr value of 0.70322 and initial εNd value of -0.4 ± 0.4 at 1805 Ma for Tistronskär monzodiorite, indicate that subcontinental lithospheric mantle source may have been metasomatized by subducted sedimentary material before the 1.80 Ga melting event.